2018
DOI: 10.1075/lia.17005.ars
|View full text |Cite
|
Sign up to set email alerts
|

L’expression des procès spatiaux causatifs chez les apprenants francophones du chinois

Abstract: RésuméCette recherche, située dans le cadre proposé par Talmy (1985,1991,2000), analyse la façon dont des apprenants francophones du chinois langue étrangère (un groupe de niveau intermédiaire et un groupe de niveau avancé) expriment les procès spatiaux causatifs, en comparaison avec des locuteurs natifs du chinois et du français. La procédure utilisée est celle d’une analyse de corpus oraux produits à partir d’une description de séquences animées. Les réponses ont été étudiées au niveau du choix des informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Ji and Hohenstein, 2014) and French (cf. Arslangul et al, 2018) L2 learners of Chinese showed that such atypical constructions, as in (38), are highly persistent even at the advanced levels of proficiency. But significantly, the child bilinguals in Tusun ( 2019) also produced such atypical constructions, exclusively with ACROSS events as well.…”
Section: Discussionmentioning
confidence: 99%
“…Ji and Hohenstein, 2014) and French (cf. Arslangul et al, 2018) L2 learners of Chinese showed that such atypical constructions, as in (38), are highly persistent even at the advanced levels of proficiency. But significantly, the child bilinguals in Tusun ( 2019) also produced such atypical constructions, exclusively with ACROSS events as well.…”
Section: Discussionmentioning
confidence: 99%